Fantasy, neoliberalism and precariousness : coping strategies in the cultural industries - Vachet, Jérémy (Digital activism and society., 2022)
A number of recent studies have responded to neoliberal understandings of entrepreneurship, creativity and innovation in the cultural and creative industries, and beyond. Although in recent years, the features of working life in this sector have been well-documented, little research seems to have looked at the psychosocial impact on the working lives of individuals. Fantasy, Neoliberalism and Precariousness draws on the results of an original empirical study of independent musicians based in Brooklyn, San Francisco, Portland, Stockholm and Paris, and considers how experiences of precariousness and insecurity under conditions of neoliberalism threatens the well-being and self-realisation of aspiring musicians. Vachet examines anxiety, narcissism, recognition and self-esteem from a sociological perspective, considering them through the lens of social class and gender. Contributing to debates within cultural studies, sociology and the political economy of communication about working lives in the cultural and creative industries, Vachet answers to-date unexplored questions around the psychosocial impact of precariousness and other problematic features of work in the cultural industries.